Isotopic evidence that recent agriculture overprints climate variability in nitrogen deposition to the Tibetan Plateau. (May 2020) - Li, Zhengjie; Hastings, Meredith G.; Walters, Wendell W.; Tian, Lide; Clemens, Steven C.; Song, Linlin; Shao, Lili; Fang, Yunting
Highlights: A 200-year record of the isotopic composition of nitrate in a Tibetan ice core. The δ 15 N-NO3 − decreases as much as 7.4‰ between the pre-industrial era to present. A holistic model was constructed to interpret the 200-year δ 15 N-NO3 − record. Fertilizer use in Asian agriculture drives significant decrease in δ 15 N after 1950. ENSO and dust events drive large interannual variability in δ 15 N throughout record. Abstract: The stable isotopes of nitrogen in nitrate archived in polar ice have been interpreted as reflecting a shift in reactive nitrogen sources or changes in atmospheric chemical reactivity. Here, we present a novel concentration and isotopic record of nitrate (δ 15 N-NO3 − ) from a central Tibetan Plateau ice core over the last ~200 years. We find that nitrate concentration increased from 6.0 ± 2.3 μeq/L (mean ± 1σ) in the preindustrial period (prior to 1900s) to 7.3 ± 2.7 μeq/L in post-1950. Over the same time period, the δ 15 N-NO3 − decreased from 8.7 ± 3.7‰ to 4.2 ± 3.1‰, with much larger interannual variation in δ 15 N-NO3 − during the preindustrial period. We present a useful framework for quantifying the sensitivity of the isotopic composition of atmospheric nitrate to changes in both sources and chemistry (gas and aerosol phase). After 1950, nitrogen deposition is primarily driven by fertilizer use, leading to significant increases in concentration and decreases in δ 15 N-NO3 − . The large interannual variability of ice core δ 15 N-NO3 − in the preindustrial reflects natural processes, namely the El Niño Southern Oscillation (ENSO) and dust events. Our results highlight a new connection between the nitrogen cycle and ENSO, and the overprinting of natural climate signals by recent anthropogenic increases in reactive nitrogen release.